Ion Dynamics at the Magnetopause of Ganymede. Issue 1 (18th January 2022) - Fatemi, S.; Poppe, A. R.; Vorburger, A.; Lindkvist, J.; Hamrin, M.
Abstract: We study the dynamics of the thermal O + and H + ions at Ganymede's magnetopause when Ganymede is inside and outside of the Jovian plasma sheet using a three‐dimensional hybrid model of plasma (kinetic ions, fluid electrons). We present the global structure of the electric fields and power density (E ⋅ J ) in the magnetosphere of Ganymede and show that the power density at the magnetopause is mainly positive and on average is +0.95 and +0.75 nW/m 3 when Ganymede is inside and outside the Jovian plasma sheet, respectively, but locally it reaches over +20 nW/m 3 . Our kinetic simulations show that ion velocity distributions at the vicinity of the upstream magnetopause of Ganymede are highly non‐Maxwellian. We investigate the energization of the ions interacting with the magnetopause and find that the energy of those particles on average increases by a factor of 8 and 30 for the O + and H + ions, respectively. The energy of these ions is mostly within 1–100 keV for both species after interaction with the magnetopause, but a few percentages reach to 0.1–1 MeV. Our kinetic simulations show that a small fraction ( < < 25%) of the corotating Jovian plasma reach the magnetopause, but among those >50% cross the high‐power density regions at the magnetopause and gain energy. Finally, we compare our simulation results with Galileo observations of Ganymede's magnetopause crossings (i.e., G8 and G28 flybys). There is an excellent agreement between our simulations and observations, particularly our simulations fully capture the size and structure of the magnetosphere. Key Points: The Hall electric field dominates at the magnetopause and in the magnetotail of Ganymede, accelerating Jovian magnetospheric ions Magnetopause interaction increases the energy of O + and H + ions by a factor of 8 and 30, respectively The incident Jovian plasma upstream of Ganymede's magnetopause is highly non‐Maxwellian and accelerated up to 1 MeV at the magnetopause